Spontaneously Resolved Recurrent Cervical Epidural Hematoma in a 37-Week Primigravida. (October 2015) - Iwatsuki, Katsuyuki; Deguchi, Masao; Hirata, Hitoshi; Kanamono, Toshihisa
Study Design: Case report. Objective: To describe a patient with a recurrent spontaneous spinal epidural hematoma (SSEH) during pregnancy that had spontaneous remission. Methods: A 27-year-old primigravida at 37 weeks' gestation suddenly felt a strong left shoulder pain without any trauma. She had a history of fenestration for a spontaneous cervical hematoma when she was 18 years old. An emergency magnetic resonance imaging revealed a recurrence of the cervical epidural hematoma at the C4–T1 level, but she had no paralysis. Results: The patient subsequently underwent a cesarean section and delivered a healthy male infant. Her spinal epidural hematoma disappeared. Multislice computed tomography showed no evidence for a vascular malformation or tumor. Three years after the initial cesarean section, she underwent a second one and delivered another male infant. Conclusions: We report on a rare case of recurrent SSEH during pregnancy with no neurologic deficits that was treated nonoperatively with close observation and resulted in spontaneous resolution. In such patients with no neurologic deficits, nonoperative management with close observation may be a reasonable alternative.